SEJARAH PEMBANGUNAN HUKUM PERBANKAN SYARIAH DI INDONESIA - Umam, Khotibul (Veritas et Justitia, 2020)
In this article the author traces the historic development of Islamic or sharia banking in Indonesia and this will be done by analysing the evolution of a series of successive laws promulgated over time.  From these laws (Law Nos. 7/1992; 10/1998 and 21/2008) we can discern, how over the years, the Indonesian government gradually accept and recognized sharia banking principles, resulting in the establishment of Sharia Banks alongside conventional Banks.  These successive laws also shows the gradual process of policy changes which involves a top-down, bottom up and again a top down approach. Through this process, Sharia Banks develops in Indonesia and has been able to meet society’s need not only for a modern banking system, but also more importantly, providing banking services in line with the sharia.